PERBEDAAN JUMLAH ERITROSIT ANTARA DARAH YANG SEBANDING DAN TIDAK SEBANDING DENGAN K2EDTA - Sinaga, Hotman; Tominik, Victoria ire; Hardiyanti, Meileni (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
One aspect of preanalytical that may affect the results of erythrocyte examination is the ratio between the volume of blood with an anticoagulant. If the blood volume is insufficient to anticoagulant causes red cells to crenated, and if the blood volume is excess to anticoagulant can cause blood clot. This research is pre experiment with static group comparison design using total sampling technique. The Subject of this research amounted to 34 residents of RT 57 RW 13 Kelurahan Kebun Bunga Sukarami District of Palembang aged 40-50 years. Each subject of research conducted about 3 mL blood sample, then the blood is divided into 2 groups is group one (0.5 mL of blood in K2EDTA tube 2 mL) and group two (2 mL of blood in K2EDTA tube 2 mL). Blood samples were then examined using a Sysmex XS-800i. The results of the examination average number of erythrocytes in blood volume of 0.5 mL and 2 mL with K2EDTA have a difference of as much as 2%. Based on this research can Wilcoxon Sign Rank test results is p=0.011 (p <0.025) is showed a difference red blood count between blood volume of 0.5 mL and 2 mL in K2EDTA tube. Keywords: Preanalytical, blood volume, K2EDTA.